A Qualitative Study of Physician Perspectives on Prognostication in Neonatal Hypoxic Ischemic Encephalopathy. (October 2016) - Rasmussen, Lisa Anne; Bell, Emily; Racine, Eric
Hypoxic ischemic encephalopathy is the most frequent cause of neonatal encephalopathy and yields a great degree of morbidity and mortality. From an ethical and clinical standpoint, neurological prognosis is fundamental in the care of neonates with hypoxic ischemic encephalopathy. This qualitative study explores physician perspectives about neurological prognosis in neonatal hypoxic ischemic encephalopathy. This study aimed, through semistructured interviews with neonatologists and pediatric neurologists, to understand the practice of prognostication. Qualitative thematic content analysis was used for data analysis. The authors report 2 main findings: (1) neurological prognosis remains fundamental to quality-of-life predictions and considerations of best interest, and (2) magnetic resonance imaging is presented to parents with a greater degree of certainty than actually exists. Further research is needed to explore both the parental perspective and, prospectively, the impact of different clinical approaches and styles to prognostication for neonatal hypoxic ischemic encephalopathy.